Very preterm infants can detect small variations in light levels in incubators. (October 2015) - Zores, Claire; Dufour, André; Pebayle, Thierry; Langlet, Claire; Astruc, Dominique; Kuhn, Pierre
Abstract Aim This prospective observational study was designed to improve our understanding of the responses of very preterm infants to light level variations in incubators and to evaluate what determined those reactions. Methods The physiological responses of 27 very preterm infants were analysed following variations in the light level environments of their incubators over 10 hours. Heart and respiratory rates, systemic oxygen saturation and regional cerebral oxygen saturations were recorded using near‐infrared spectroscopy, and the variation of each parameter was analysed. Results We analysed 332 light level changes. Heart rate increased by 3.8 beats per minute (range −2.6 to 12.6), respiratory rate by six cycles per minute (−1.5 to 26) and regional cerebral oxygen saturation by 1.1% (−0.5% to 3.9%) (p < 0.05 each) when delta lux was over 50. Only respiratory rate decreased significantly, by −8.4 cycles per minute (−28 to −0.4), when delta lux was 50 or lower (p < 0.05). The initial level of illumination altered the very preterm infants' responses, with higher reactivity for higher ambient light levels. Conclusion Very preterm infants reacted to moderate variations in illumination in their incubator, within recommended ranges of light levels, suggesting that they may detect even small light level variations.